Sustained HIV-1 remission after heterozygous CCR5Δ32 stem cell transplantation - Christian Gaebler; Samad Kor; Kristina Allers; Michela Perotti; David Mwangi; Karolin Meixenberger; Kirsten Hanke; Timo Trenkner; Tom Kraus; Yeqin Sha; Carmen Arentowicz; Stanley Odidika; et al. (Nature, 2026)
Abstract HIV cure is exceptionally rare, with only six cases documented among the estimated 88 million individuals who have acquired HIV since the onset of the epidemic 1–6 . Successful cures, including that of the pioneering individual known as the Berlin patient, are limited to those who received allogeneic stem cell transplants (allo-SCTs) for haematological cancers. HIV resistance from stem cell donors with the rare homozygous CCR5Δ32 mutation was long considered the main mechanism for HIV remission without antiretroviral therapy. However, recent reports have highlighted CCR5-independent mechanisms as important contributors to HIV cure 6–8 . Here we provide new evidence for this conceptual shift, whereby long, treatment-free HIV remission was achieved after allo-SCT with functionally active CCR5. A man with heterozygous CCR5 wild-type/Δ32 living with HIV received allo-SCT from a HLA-matched unrelated heterozygous CCR5 wild-type/Δ32 donor as treatment for acute myeloid leukaemia. Three years after allo-SCT, the patient discontinued antiretroviral therapy. So far, HIV remission has been sustained for more than 6 years with undetectable plasma HIV RNA. Reservoir analysis revealed intact proviral HIV before transplantation, but no replication-competent virus in blood or intestinal tissues after allo-SCT. Declining or absent HIV-specific antibody and T cell responses support the absence of viral activity. High antibody-dependent cellular cytotoxicity activity at the time of transplantation may have contributed to HIV reservoir clearance. These results demonstrate that CCR5Δ32-mediated HIV resistance is not essential for durable remission, which underscores the importance of effective viral reservoir reductions in HIV cure strategies.